Kajian Teoritis Kedudukan Perusahaan Pembiayaan Leasing Terhadap Aktifitas Tindak Pidana Pencucian (Money Laundring) Terkait Dengan Penerapan Prinsip Pengenalan Nasabah (Know Your Customer) - Fontian Munzil (Jurnal Media Justitia Nusantara, 2016)
Legal standing of leasing company other than the Bank is required to anticipate money laundering crimes including detection of service users by applying the know your customer principles. This study aims to examine, first, how is the position of the law of leasing company against money laundring activities? second, how far is the obligation of leasing company to apply the know your customer principles related to the legislation in the field of money laundering. The research method used is normative juridical with descriptive analysis analysis specifications. The technique of data collection is done through reviewing data obtained from secondary data using primary, secondary, tertiary legal materials. Comparative methods of law are used to sharpen the study of the problems under study. Data analyzed qualitatively by juridical then described and presented structurally and scientifically so that analysis can be done in the form of descriptive analytical problem translation.The study found that, firstly, the legal standing of a leasing company was clear, namely as a reporter for suspicious transactions carried out by service users and this arrangement was in line with the legislation group related to money laundering crime, secondly,leasing company were required in detail in the scope of substance or formal technical (reporting) to apply the know your customer principle and will be penalized if it does not fulfill these obligations.